The Relationship Between Instructors’ Professional Competence and Student Participation in the Khenshusei Program at the Yaruki Vocational Training Center in Lubuk Alung - Annisa Latifa; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study was to examine the relationship between instructors’ professional competence and learners’ participation in the Kenshusei Program at LPK Yaruki Lubuk Alung. This study adopted a quantitative method utilizing a correlational research design. The research subjects consisted of participants in the Kenshusei Program, selected through a sampling technique appropriate to the population characteristics. Data collection was carried out by distributing questionnaires, and the obtained responses were processed through the Product Moment correlation analysis. The findings demonstrate a statistically significant link between instructors’ professional competence and learners’ participation levels. This indicates that as instructors’ professional competence increases, learner involvement in the training program also tends to rise.Therefore, strengthening instructors’ professional competence is a strategic factor in optimizing learners’ participation.